Treatment of Gait and Sensory Changes in Experimental Disc Herniation Radiculopathy by Local and Sustained Anticytokine Delivery. Issue 1 (April 2016) - Shamji, Mohammed
Objective: Disc-herniation induced radiculopathy arises from both mechanical compression and biochemical inflammation of apposed neural elements. The mechanisms that underlie evolution of a painful neuropathy remain undefined. This in vitro and in vivo study demonstrated the effect of nucleus pulposus (NP) material toward inflammatory activation and defined the need for intraneural macrophage migration after placement heterotopic disc tissue to generate the painful neuropathy phenotype. Methods: In vitro analysis involved evaluating the mouse peritoneal macrophage response to NP-conditioned media for neurotrophin expression (mRNA by PCR) and inflammatory activation (nitric oxide by Greiss reaction). In vivo work involved C57BL/6 mice underwent a surgical procedure with mid-thigh exposure of the sciatic nerve. Control animals underwent exposure only ( n = 12) and experimental animals underwent placement of littermate tail nucleus pulposus (NP, n = 12). Animals were evaluated throughout one week for mechanical allodynia by Von Frey testing, thermal hyperalgesia by heat withdrawal latency, cold allodynia by acetone testing, and gait stability by RotaRod testing. At sacrifice, immunohistochemistry was performed to identify perineural and intraneural macrophage and lymphocyte presence. Necessity of intact macrophage activity was tested using a tamoxifen-induced CreER macrophage-selective BDNF knockout system and bisphosphonate-induced macrophage depletion. Results: Peritoneal macrophages exposed to NP-conditioned media exhibited progressively heightened levels of nitric oxide production as well as heightened neurotrophin expression at 72 hours. Mice exposed to heterotopic NP stimulation demonstrated substantial mechanical allodynia, thermal hyperalgesia, and cold allodynia compared with controls. Intraneural macrophage infiltration was observed in this group, alongside associated autoreactive lymphocytes at the disc-nerve interface. Macrophage depletion using bisphosphonate-containing liposomes prevented both perineural accumulation and intraneural migration of macrophages as well as evolution of the painful phenotype. Knocking out inflammatory cell BDNF activity in the CreER animals still permitted perinenural macrophage accumulation but eliminated intraneural macrophage migration as well as evolution of the painful phenotype. Conclusion: Disc NP material induces inflammatory activation among macrophages as well as upregulated neurotrophin expression. Non-compressive disc herniation leads to altered behavior in this animal disease model, with demonstrated need for intraneural macrophage migration. Strategies to decrease perineural inflammation or maintain integrity of the blood nerve barrier may be effective in treating painful disc-herniation radiculopathy. References Sinclair SM, Shamji MF, Chen J, et al. Attenuation of inflammatory events in human intervertebral disc cells with a tumor necrosis factor antagonist. Spine 2011;36(15):1190–1196 Shamji MF, Allen KD, So S, et al. Gait abnormalities and inflammatory cytokines in an autologous nucleus pulposus model of radiculopathy. Spine 2009;34(7):648–654